Mengungkap Transparansi Dan Akuntabilitas Pengelolaan Keuangan Upacara Ngusabha Nini Yang Dilandasi Dresta Desa Adat Tegenan - Ni Kadek Ratna Dewi; Lucy Sri Musmini (Jurnal Akuntansi Profesi, 2020)
This study discusses the application of the principles of transparency and accountability   in the financial management of the ngusabha nini ceremony by krama seket based on dresta Desa Adat Tegenan. The research method used is a qualitative research method in which data collection is carried out directly through field observation, interviews, and documentation studies. The results of this study indicate that 1) The financial management of the ngusabha nini ceremony is managed by the prajuru krama seket and is carried out through three stages, namely the planning stage, the implementation phase, and the accountability stage. The implementation of financial management is carried out in accordance with the rules of uger-uger krama seket. 2) The principle of transparency in financial management is applied through the tradition of pesangkepan or joint meetings conducted by the krama seket and supported by the role of the kasinoman or juru arah. 3) Accountability for the financial management of this ngusabha nini ceremony is done by making simple records related to the number of income and expenses without making financial reports. Information related to the amount of fund income and fund disbursement is published verbally to the krama seket and is in accordance with the existing elements of accountability.